COMMUNITY-BASED SANITATION PROGRAM (SANIMAS) AS AN EFFORT FOR IMPROVING ENVIRONMENTAL QUALITY IN URBAN SLUM SETTLEMENTS - Winny Astuti (Journal of Architecture&ENVIRONMENT, 2016)
The second theme of the UN Conference on Human Settlements II in Istanbul in 1996 was sustainable human settlements development in an urbanizing world, which stated that waste is among ten important issues needing to be addressed. Apart from that the Post Agenda 2015 Goal 6 was to ensure availability and sustainable management of water and sanitation for all. Indonesia, where urbanization has grown significantly over recent years, is facing a waste problem. The central government released Sanimas program, which aimed to build sanitation infrastructure to upgrade its provision in urban settlements and to improve settlements’ environmental quality. Sanimas specifically targeted dense and poor urban settlements. In Surakarta, the program was implemented in 2006, Sanimas constructed public toilets and a communal wastewater treatment facility at Kelurahan Sangkrah,. This paper was designed to identify Sanimas’ implementation process and the networks of the related institution. This inductive research was based oninstitutions related to the program’s implementation and triangulation with secondary data.The research found that the implementation of the Sanimas Program has established a Community-based Organisation named KSM, which mediates between the local government and the community. Through KSM, inter-organisational networks have been developed, which indicated expanding linkages of the community to several organisations, and to higher level government and foreign agencies. Inter-organisational networks sustain the program, improve the quality of environment as well as increase community capacity.